2010
DOI: 10.1089/dia.2009.0085
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Ligament Remodeling and Alveolar Bone Resorption During Orthodontic Tooth Movement in Rats with Diabetes

Abstract: Under mechanical forces, diabetes prolonged duration of degradation of PDL and remodeling of PDL and resorption of alveolar bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 39 publications
7
44
0
12
Order By: Relevance
“…Some previous studies indicated a decrease in the number of osteoclasts in type 1 diabetic rodent (20)(21)(22). On the other hand, several groups have reported higher levels of TRAP activity and an increased number of osteoclasts was observed in type 1 diabetic rodent (23)(24)(25)(26). In this regard, this study aimed to investigate the potential effect of insulin on RANKL and OPG expression in osteoblasts for the purpose of investigating the effect of insulin on osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Some previous studies indicated a decrease in the number of osteoclasts in type 1 diabetic rodent (20)(21)(22). On the other hand, several groups have reported higher levels of TRAP activity and an increased number of osteoclasts was observed in type 1 diabetic rodent (23)(24)(25)(26). In this regard, this study aimed to investigate the potential effect of insulin on RANKL and OPG expression in osteoblasts for the purpose of investigating the effect of insulin on osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…19 Rapid bone resorption and marked PDL destruction are features of orthodontic movement in animal models of diabetes in a study done by Li et al, 2 with significantly more osteoclasts in the PDL of diabetic induced rats compared with normoglycemic rats after orthodontic treatment. Graber et al 20 stated that TNF-α plays a prominent role in the mechanism controlling the appearance of osteoclasts at compression sites.…”
Section: Discussionmentioning
confidence: 99%
“…1 The change in the metabolic state interferes with bone remodelling and results in a different rate of tooth movement. 2 Braga et al 3 reported greater tooth movement with retarded osseous regeneration, debilitation of the periodontal ligament, and microangiopathies in diabetic experimental mice when compared with the normal group. Diabetes affects the periodontium through cytokine dysregulation, where poor glycemic control is significantly correlated with the greater production of cytokines and higher cytokine levels in gingival fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetes condition, there is an increased production of AGEs (advanced glycation end products), ROS (reactive oxygen species) and TNF, which affects the development of periodontal disease [8]. Volume Metabolic changes (such as diabetes) can interfere with bone remodeling that can lead to differences in the rate of tooth movement [9,10]. Diabetes affects osteoblasts, fibroblasts, and collagen expression, through the process of inflammation and apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%